2012
DOI: 10.1111/j.1365-3032.2012.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils of citrus fruit stimulate oviposition in the Mediterranean fruit fly Ceratitis capitata (Diptera: Tephritidae)

Abstract: Female Mediterranean fruit flies (medfly) Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) perceive both qualitative and quantitative aspects of citrus fruit chemistry. However, the behavioural and biological adjustments of this response remain largely unknown. In the present study, the ovipositional responses of gravid female medflies to essential oils (i.e. the most critical resistance factor to medfly infestation) of various citrus fruits are investigated. In dual‐choice (treatment versus distilled wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 42 publications
3
44
0
1
Order By: Relevance
“…This fact was observed by Ioannou et al (2012) who identified that compounds like linalool, found in different contents in citrus, is associated with mortality of immature stages of C. capitata, while limonene, found in more than 90% in all citrus oils, stimulates oviposition justifying infestations of C. capitata in citrus fruits.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This fact was observed by Ioannou et al (2012) who identified that compounds like linalool, found in different contents in citrus, is associated with mortality of immature stages of C. capitata, while limonene, found in more than 90% in all citrus oils, stimulates oviposition justifying infestations of C. capitata in citrus fruits.…”
Section: Discussionmentioning
confidence: 71%
“…The flavedo constitution is cited by several authors as the most critical resistance mechanism to fruit flies infestation in citrus (Back and Pemberton, 1915;Greany et al, 1983;Salvatore et al, 2004;Ioannou et al, 2012). Possibly, when oil glands in the flavedo are broken, they release toxic compounds that, in contact with eggs and first instar larvae, can cause death before the larvae reach the albedo region (non-oily region of the peel) (Greany, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Limonene was selected among the three compounds tested because (as mentioned above) it is the most abundant compound of citrus EOs [2, 14]. Subsequently, flies were sorted by treatment and kept in 20 by 20 by 20 cm Plexiglas cages.…”
Section: Methodsmentioning
confidence: 99%
“…As citrus fruits mature from an immature green to an orange/yellow mature stage, the linalool content of the peel oil declines progressively, and the less toxic limonene becomes the major component. Limonene content acts as a potential stimulus for the ovipositional responses observed with sweet orange oil, whereas high linalool contents could mask or disrupt those effects in citrus oils (Ioannou et al 2012).…”
Section: Genus Ceratitismentioning
confidence: 99%
“…Limonene, the most abundant chemical in citrus essential oils, stimulates oviposition in C. capitata females, whereas linalool, a compound representative of immature citrus fruit associated with high toxicity against immature stages of fruit flies and considered as an important compound conferring resistance against fruit fly larval development, has a significant deterrent effect (Ioannou et al 2012). As citrus fruits mature from an immature green to an orange/yellow mature stage, the linalool content of the peel oil declines progressively, and the less toxic limonene becomes the major component.…”
Section: Genus Ceratitismentioning
confidence: 99%